1994
DOI: 10.5144/0256-4947.1994.139
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ramadan Fasting on Certain Biochemical Parameters in Normal Subjects and in Type II Diabetic Patients

Abstract: Fasting levels of cholesterol, triglycerides, uric acid, fructosamine and glycosylated hemoglobin were measured in normal and in Type II diabetic subjects before the beginning and at the end of the Muslim month of fasting (Ramadan). In normal subjects, there was a significant increase (P<0.01) in triglycerides and uric acid levels as a result of Ramadan fasting. In diabetic patients, triglyceride levels decreased significantly (P<0.05), while uric acid levels showed a significant increase (P<0.01) as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…17 Al-Hader et al showed a significant increase in TG without any significant change in T-C after fasting in healthy subjects. 20 Maisols et al showed a striking (>30%) nonpharmacologicimprovement in plasma HDL-C concentration with fasting and attributed it to eating one large meal a day (gorging). Plasma concentrations of TG, T-C, LDL-C and HDL-C did not change, but TC:HDL cholesterol and LDL:HDL cholesterol ratios did decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
“…17 Al-Hader et al showed a significant increase in TG without any significant change in T-C after fasting in healthy subjects. 20 Maisols et al showed a striking (>30%) nonpharmacologicimprovement in plasma HDL-C concentration with fasting and attributed it to eating one large meal a day (gorging). Plasma concentrations of TG, T-C, LDL-C and HDL-C did not change, but TC:HDL cholesterol and LDL:HDL cholesterol ratios did decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Most patients show no change in their glucose control. In some patients, serum glucose concentration may fall or rise, which may be due to the amount or type of food consumed, changes in body weight and exercise habits, regularity of taking medications, or engorging after the fast is broken.…”
Section: Diabetesmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] The amount of fructosamine, insulin and C-peptide has been reported to have no significant change before and during Ramadan fasting. 23,27,28 Serum creatinine, uric acid, blood urea nitrogen, protein, albumin, alanine amino-transferase, and aspartate amino-transferase values do not show significant changes during the fasting period. 27,30 The amount of energy (calorie) intake have been reported in some of the literature, indicating a decrease in energy intake.…”
Section: Diabetesmentioning
confidence: 99%
“…More studies show no change or a slight decrease in concentrations of total cholesterol and triglycerides [19][20][21] . Increase in total cholesterol levels during Ramadan seldom occurs [22] .As in healthy persons [4,6] .Few studies have reported increases in high-density-lipoprotein (HDL) cholesterol in diabetics during Ramadan [23,24] . One report indicates an increase in low-density-lipoprotein (LDL) cholesterol and a decrease in HDL-cholesterol [18] .Few studies have shown the effect of Ramadan fasting Serum creatinine, uric acid, blood urea nitrogen, protein, albumin, alanine amino-transferase; aspirate amino-transferase values do not show significant changes during the fasting period [19,21,25] .…”
Section: Introductionmentioning
confidence: 99%
“…Many physiological and psychological changes take place during Ramadan, most probably due to the changes in eating patterns, eating frequency and sleep patterns [4] . Some studies in the eastern Mediterranean area have indicated improved high-density lipoprotein (HDL) cholesterol during Ramadan fasting [5,6] . Few studies have shown the effect of Ramadan fasting on serum glucose [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%